Respuesta :

Answer:

        b = -2

Step-by-step explanation:

The point-slope form of equation is: y - y₀ = m(x - x₀), where (x₀, y₀) is any point the line passes through and m is the slope.

m = 2

(4, 6)    ⇒   x₀ = 4,  y₀ = 6

So, the point-slope form of equation:

y - 6 = 2(x - 4)

Changing to the slope-intercept form of the equation of the line (y = mx + b, where m is the slope and b is the y-intercept of the line):

y - 6 = 2x - 8               {add 6 to both sides}

y = 2x - 2    ⇒  b = -2